Pengaruh Entrepreneurial Orientation dan Task Environment terhadap Kinerja UMKM Kota Medan - Imelda Sitinjak (Journal of Economic and Business, 2020)
This study aims to determine the effect of entrepreneurial orientation (EO) and task environment on the performance of UKM Kota Medan. The sampling method is purposive sampling with the criteria for owners which SMEs are registered in the Medan City Cooperative and UKM Office in 2019, and have been operating for at least 1 year in Medan City. Data obtained from 100 SME owners as respondents were then analyzed using the Structural Equation Model with the Lisrel computer program. The results show that the task environment has a positive and significant effect on the business performance of Medan City SMEs, while the entrepreneurial orientation does not. This study reinforces the justification of previous studies that external influences such as positive and significant task environments on internal conditions such as the performance of a business and also justification that there are inconsistencies in the influence of entrepreneurial orientation on business performance. The implication for Medan City SMEs is to anticipate future changes by paying attention to any changes in the environment (task environment), also using entrepreneurial orientation in formulating business strategies so as to improve the performance of a business. Suggestions for further studies are examining the effect of each dimension of entrepreneurial orientation on performance, adding control variables, or mediation, or moderation, or antecedents in examining the relationship between EO and SME performance, or researching in industries that are currently experiencing a lot of environmental changes.